Potensi Pembangkitan listrik hybrid menggunakan vertical axis wind turbine tipe Savonius dan panel surya - Winarto, Felixtianus Eko Wismo (IST Akprind, 2013)
The use of fossil energy for conventional power plants in the long time will run out oil, gas and coal reservoir. Therefore the renewable energy utilization that more environmentally friendly and renewable concepts such as wind and solar heat should be optimized. Two kind of potensial renewable energy resources in Indonesia that should be optimized are wind power and solar energies, They will be complement each other, in the dry season the sun will be role while in the rainy season wind power will be more dominant. This hybrid concept combining solar cell panels and Savonius turbine to gain a greater electrical output than the solar cell panels and Savonius wind turbine that operate in their owntask. A single stage Savonius wind turbines are made three design types to find the best design that can convert more energy from any wind direction. A Solar cell panel is placed under the sun to produce current and voltage from sun light. The energy summation data will be recorded by Data Aquisition System. From the measurement and data analysis results, the electrical power generated by prototype of hibrid system is 7.5 watt. This value is greater if compare to the power generated by solar panelsand wind turbines separatelly.